Ọmọ Tí A Kò Kọ́: Globalization and Cultural Education among New Generation Nigerian Yorùbá - Michael O. Afolayan (Yoruba Studies Review)
This essay critically explores the semantic, phonological and philosophical implications of the sound “kọ” (build) in the Yorùbá proverb  ́ Ọmọ tí a kò kọ́ ni yóò gbé ilé tí a kọ́ tà (the child that is not taught will eventually sell the house that is built). I will read the concept behind the sound as a multi-layered, multi-semantic meta-philosophical building block which not only showcases a serious aspect of indigenous epistemology and serving as a note of caution on Yorùbá education and its sociology of filial responsibilities, but could also be deployed to interrogate the emerging youth culture of the new generation Nigerian Yorùbá in the age of globalization. The essay draws on the semantic and philosophical content of kọ́ to articulate the argument that investments on material possession are counterproductive and antithetic to investment on human capital, the epitome of which is investing on one’s child/ ren. The essay concludes that the spirituality and permanency of the kọ of the ́ child’s mind is diagonally opposed to the superficiality and transience of the kọ́ of the building, a mere structure with limited value.